Village circumambulation dhikr as a medium of cultural da’wah and Islamic social communication among the community - Idawati Idawati; Ahmad Tamrin Sikumbang; Tessa Shasrini (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2026)
This study aims to analyze the practice of village circumambulation dhikr as a medium of cultural da’wah and Islamic social communication in Medang Kampai District, Dumai City, Riau Province. This tradition represents a form of da’wah bil hal (action-based da’wah) that integrates Islamic values with the local wisdom of the coastal Malay community. The study employed a qualitative method with a phenomenological approach through field observations, in-depth interviews with religious and community leaders, and documentation of the ritual activities. The findings reveal that the village circumambulation dhikr is conducted regularly through the active participation of community members who collectively walk around the village under the guidance of religious leaders. This collective action serves not only as a religious practice but also as a social space that fosters Islamic brotherhood, social solidarity, mutual care, and a stronger sense of community belonging. As a form of cultural da’wah, the tradition communicates Islamic values through social action, exemplary conduct, and communal participation, allowing religious messages to be conveyed in a contextual and inclusive manner. In addition to strengthening religious identity, the practice contributes to social harmony, community cohesion, and collective awareness of the importance of a peaceful and spiritually grounded life. Therefore, village circumambulation dhikr demonstrates that culturally rooted da’wah bil hal remains a relevant and effective model of Islamic communication in contemporary society. ***** Penelitian ini bertujuan menganalisis praktik zikir keliling kampung sebagai media dakwah kultural dan komunikasi sosial Islam di Kecamatan Medang Kampai, Kota Dumai, Provinsi Riau. Tradisi ini merupakan bentuk dakwah berbasis tindakan kolektif (dakwah bil hal) yang memadukan nilai-nilai Islam dengan kearifan lokal masyarakat Melayu pesisir. Penelitian menggunakan metode kualitatif dengan pendekatan fenomenologis melalui observasi lapangan, wawancara mendalam dengan tokoh agama dan tokoh masyarakat, serta dokumentasi kegiatan. Hasil penelitian menunjukkan bahwa zikir keliling kampung dilaksanakan secara rutin dengan melibatkan partisipasi aktif masyarakat yang berjalan bersama mengelilingi lingkungan permukiman di bawah bimbingan tokoh agama. Aktivitas kolektif tersebut tidak hanya menjadi sarana ibadah, tetapi juga membangun ruang interaksi sosial yang memperkuat ukhuwah Islamiyah, solidaritas, kepedulian sosial, dan rasa memiliki terhadap komunitas. Tradisi ini berfungsi sebagai media dakwah kultural yang mengkomunikasikan nilai-nilai Islam melalui tindakan nyata, keteladanan, dan partisipasi sosial, sehingga pesan-pesan keagamaan diterima secara lebih kontekstual dan inklusif. Selain memperkuat identitas religius masyarakat, zikir keliling kampung juga berkontribusi dalam menciptakan harmoni sosial, memperkokoh kohesi komunitas, dan menumbuhkan kesadaran kolektif terhadap pentingnya kehidupan yang religius dan damai. Dengan demikian, tradisi ini menunjukkan bahwa dakwah bil hal yang berbasis budaya lokal tetap relevan sebagai model komunikasi Islam yang efektif dalam kehidupan masyarakat kontemporer.